Volume 6B: Materials and Fabrication 2013
DOI: 10.1115/pvp2013-97431
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Fracture Modelling for RPV Steels: Discrete Model for Collective Behaviour of Micro-Cracks

Abstract: The ability to predict variations in cleavage fracture toughness behaviour of ferritic RPV steels, accounting for the effects of irradiation and defect geometry, is vital to safety assessment and life extension decisions. Local approaches to cleavage fracture offer a promising methodology to accomplish such calculations. However, the limited progress achieved by improving the local failure probability expression suggests that the methodology for calculating global cleavage might not be adequately representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The value of the T-stress depends on crack size, geometry, and the traction parallel to the crack plane; also, it has an effect on plastic zone size and crack tip opening displacement [36]. Further studies showed that compressive T-stress can reduce the crack tip constraint which is followed by an increase in fracture toughness [37][38][39]. Very close to the crack tip (đť‘ź → 0), the first term on the right hand of equation 2.1 exhibits a singularity and the equation's value tend to infinity, which means the rest of the terms can be ignored and simplify the equation 2.1 as:…”
Section: -2-1 Linear Elastic Fracture Mechanics (Lefm)mentioning
confidence: 99%
“…The value of the T-stress depends on crack size, geometry, and the traction parallel to the crack plane; also, it has an effect on plastic zone size and crack tip opening displacement [36]. Further studies showed that compressive T-stress can reduce the crack tip constraint which is followed by an increase in fracture toughness [37][38][39]. Very close to the crack tip (đť‘ź → 0), the first term on the right hand of equation 2.1 exhibits a singularity and the equation's value tend to infinity, which means the rest of the terms can be ignored and simplify the equation 2.1 as:…”
Section: -2-1 Linear Elastic Fracture Mechanics (Lefm)mentioning
confidence: 99%